2018
DOI: 10.3389/fpsyg.2018.01566
|View full text |Cite
|
Sign up to set email alerts
|

Not All Phrases Are Equally Attractive: Experimental Evidence for Selective Agreement Attraction Effects

Abstract: Research on memory retrieval during sentence comprehension suggests that similarity-based interference is mediated by the grammatical function of the distractor. For instance, Van Dyke and McElree (2011) observed interference during retrieval for subject-verb thematic binding when the distractor occurred as an oblique argument inside a prepositional phrase (PP), but not when it occurred as a core argument in direct object position. This contrast motivated the proposal that constituent encodings vary in the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 64 publications
(215 reference statements)
1
48
0
Order By: Relevance
“…Overall, the data cleaning did not affect more than 15% of the data (Ratcliff, 1993) in Experiment 1 (Supplementary Material S3). The regions analyzed were R3 (the region of the Head/pre-critical region), R4 (the region of the Attractor/first critical region), R5 (the region of the agreement target/second critical region), and the post-critical regions, namely R6 and R7 (for potential spillover effects), similar to previous attraction studies (e.g., Wagers et al, 2009;Lago et al, 2015;Slioussar and Malko, 2016;Parker and An, 2018). RTs were log-transformed in all models.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the data cleaning did not affect more than 15% of the data (Ratcliff, 1993) in Experiment 1 (Supplementary Material S3). The regions analyzed were R3 (the region of the Head/pre-critical region), R4 (the region of the Attractor/first critical region), R5 (the region of the agreement target/second critical region), and the post-critical regions, namely R6 and R7 (for potential spillover effects), similar to previous attraction studies (e.g., Wagers et al, 2009;Lago et al, 2015;Slioussar and Malko, 2016;Parker and An, 2018). RTs were log-transformed in all models.…”
Section: Discussionmentioning
confidence: 99%
“…This is the measure of the attraction effect we aim to simulate. Parker and An (2018) found that this effect was smaller when the attractor appeared in a core argument like in Ex. 8 than when it appeared in an oblique argument as in Ex.…”
Section: Agreement Attraction In Comprehensionmentioning
confidence: 96%
“…Core arguments, due to their importance to interpretation, have been argued to be encoded more carefully than their less-critical oblique counterparts (Van Dyke & McElree, 2011). Parker and An (2018) predict that this would lead to stronger attraction effects from attractors in oblique arguments, as the poor encoding may cause the attractor to be more easily confused with the subject. Parker and An (2018) tested this hypothesis in a self-paced reading study using materials such as the following: Figure 6: Human and simulation results for Parker and An (2018).…”
Section: Agreement Attraction In Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations